(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2012)
The theoretical elaboration offered by Gérard Genette on the modes of artwork transcendence and on the aesthetical relationship is today an explicative platform for understanding the trans- formation of the DVD viewer into a kind of “philologist,” who accesses different versions, languages and subtitles, and a variety of extras (director’s commentaries, documentaries on the production, interviews, trailers, cut scenes and other paratexts). Moreover, the movie can become a cultural object that is placed in a web of productions in a “crossmedial” project. The problematisation of the cinematographic identity, already created by the transformation of the supports, seems to motivate the urgency perceived by Genette of reactualising the theory of Nelson Goodman. Nevertheless, it is worth pointing out the full overcoming of the identifica- tion between work and text (following the approach of the aesthetical analysis) or on the con- trary, we can underline how such a web of objects of immanency participate to build a corpus of texts that makes philology, to a certain extent, part of the spectatorial language-game.